AUTHORITY OF NOTARY AND THE POWER OF LAW POSTNUPTIAL AGREEMENT DEED POST-DECISION OF CONSTITUTIONAL COURT NUMBER: 69/STATUTORY REGULATIONS-XIII/2015 - Made Widyadi (NOTARIIL Jurnal Kenotariatan, 2019)
This research aims is to increase knowledge and insight about Notary Authority and Legal Strength of Postnuptial Agreement Deed Post Constitutional Court Decision Number: 69/Statutory Regulations-XIII/2015. Normative research method, reviewing the legislation and library materials with approaches of legislation and concepts, the source of legal materials using primary, secondary and tertiary legal materials, after the legal material collected through literature study then further analyzed by qualitative descriptive to get a conclusion. The result of the research obtained is the Notary Authority in the aggregation of the Postnuptial Agreement Deed after the Constitutional Court Decision Number: 69/Statutory Regulations-XIII/2015 is a Notary authorized to make Postnuptial Agreement Deed whose contents are retroactive. Post-Decision of the Constitutional Court The Postnuptial Agreement made by a new notary has the legal power after being registered with the Civil Registry Agency based on Regulation of the Minister of Home Affairs Number 472.2/5876/Department Of Population And Civil Registration.